Analysis of the 2013 Curriculum and the Independent Curriculum on Changes and Impacts in the Development of the Islamic Education Curriculum - Muhammad Irfansyah Siregar; Tasya Amelia Putri Siregar; Siti Halimah (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to determine the differences between the 2013 curriculum and the independent curriculum. The differences analyzed in this research are the differences in SKL (Graduate Competency Standards), SI (Content Standards), SP (Process Standards), and Evaluation Standards in the 2013 curriculum and the independent curriculum.In this research, the method used is a descriptive qualitative method, namely through literature study using literature sources that are relevant and helpful for research. The results of this research show that there are several things that are similarities and differences between the 2013 curriculum and the independent curriculum which is proof that the change in the curriculum from the 2013 curriculum to the independent curriculum is an effort to improve the education curriculum in Indonesia, namely by bringing the good things from the 2013 curriculum and throw away irrelevant things and replace them with better things in the independent curriculum.